PENDIDIKAN ISLAM PADA ANAK USIA DINI DALAM PERSPEKTIF ABDULLAH NASHIH ULWAN : (Tela’ah atas Kitab Tarbiyah Al-Aulād Fī Al-Islām) - Shofiyati Shofiyati; Sumiyati Sumiyati (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2021)
This study discusses about early childhood Islamic education according to Abdullah Nashih Ulwan in the book Tarbiyah Al-Aulād Fī Al-Islām which is motivated by the problems of parenting teachers and parents in educating early childhood. The results of this study are expected to contribute thoughts and ideas to increase knowledge about Islamic education in early childhood from various leading experts who focus on early childhood education. This research is aresearch method Critical Discourse Analysis (CDA)that uses a discourse analysis approach and texts from the Norman Fairclough model, which is an approach that try to explain and reflect carefully on Abdullah Nashih Ulwan's thoughts on the method of Islamic education in early childhood in the book Tarbiyah Al-Aulād. Fī Al-Islam. The results of this study show: first, the methods of early childhood education according to Abdullah Nashih Ulwan are: Educating by example, educating with habits, educating with advice, educating with attention, and educating with punishment. Second, early childhood education according to Abdullah Nashih Ulwan is: faith education, moral education, physical education, intellectual education, mental education, social education, and sex education.